Topology Optimization for Low-Power-Wide-Area Networks (LPWANs) within Internet of Things (IOT) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Low-Power Wide-Area Networks (LPWANs) have emerged as a critical enabler for large-scale Internet of Things (IoT) deployments due to their long-range communication capabilities and low energy consumption. However, achieving optimal performance in LPWAN-based IoT systems requires careful network topology design to balance energy efficiency, coverage, scalability, and reliability. This paper investigates topology optimization strategies tailored for LPWANs, focusing on technologies such as LoRaWAN, NB-IoT, and Sigfox. We propose a multi-objective optimization framework that considers node placement, gateway density, data traffic patterns, and energy constraints. By applying both simulation and analytical modeling, we showcase notable enhancements in network longevity, delay performance, and packet delivery efficiency. Our results provide practical guidelines for deploying scalable and sustainable LPWAN topologies in diverse IoT applications, ranging from smart cities to remote environmental monitoring.